2020
DOI: 10.1177/0267659120934612
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged duration of repolarization and decreased conduction velocity in the atrial myocardium after hypothermic ischemia-reperfusion may be related to expressions of inward rectifier potassium channel 2.1 protein and connexin 40

Abstract: Objectives: The study aimed to determine the role of inward rectifier potassium channel 2.1 protein and connexin 40 expressions in regulating the duration of repolarization and conduction velocity of right atrial myocardium in rats following hypothermic ischemia-reperfusion. Methods: The Langendorff isolated rat cardiac perfusion models were divided into control (C) and hypothermic ischemia-reperfusion gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Related experiments have shown that the connexin 40 promoter has a binding site for Nkx2.5, and in vivo transcriptional activation studies have shown that Nkx2.5 can activate the expression of the connexin 40 promoter ( 115 ). What's more, mutations in the Nkx2.5 gene lead to apoptosis of autorhythmic cells, which may also be the cause of the arrhythmia ( 115 ). 15% of patients with sudden cardiac death have inherited atrial septal defect and atrioventricular block ( 116 ).…”
Section: Association Of Nkx25 Mutations With Heart Diseasementioning
confidence: 99%
“…Related experiments have shown that the connexin 40 promoter has a binding site for Nkx2.5, and in vivo transcriptional activation studies have shown that Nkx2.5 can activate the expression of the connexin 40 promoter ( 115 ). What's more, mutations in the Nkx2.5 gene lead to apoptosis of autorhythmic cells, which may also be the cause of the arrhythmia ( 115 ). 15% of patients with sudden cardiac death have inherited atrial septal defect and atrioventricular block ( 116 ).…”
Section: Association Of Nkx25 Mutations With Heart Diseasementioning
confidence: 99%